2022
DOI: 10.3390/nu14245212
|View full text |Cite
|
Sign up to set email alerts
|

Lactiplantibacillus plantarum DSM20174 Attenuates the Progression of Non-Alcoholic Fatty Liver Disease by Modulating Gut Microbiota, Improving Metabolic Risk Factors, and Attenuating Adipose Inflammation

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease, reaching epidemic proportions worldwide. Targeting the gut–adipose tissue–liver axis by modulating the gut microbiota can be a promising therapeutic approach in NAFLD. Lactiplantibacillus plantarum, a potent lactic-acid-producing bacterium, has been shown to attenuate NAFLD. However, to our knowledge, the possible effect of the Lactiplantibacillus plantarum strain DSM20174 (L.p. DSM20174) on the gut–adipose tissue axis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Despite the increasing global prevalence of obesity, there is a lack of effective treatment strategies. Although various medications are presently used to address severe obesity and associated metabolic conditions [ 26 ], efforts are needed to reduce the adverse effects of these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increasing global prevalence of obesity, there is a lack of effective treatment strategies. Although various medications are presently used to address severe obesity and associated metabolic conditions [ 26 ], efforts are needed to reduce the adverse effects of these drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the long-term administration of high-fat diets induce fat accumulation and stimulate liver fibrosis [ 29 ]. Previous studies reported that L. plantarum DSM20174 reduced the progression of non-alcoholic fatty liver disease by gut microbiota modulation and improved lipid accumulation and adipose tissue inflammation [ 30 ]. Therefore, body weight gain, visceral organ indexes, lipid profiles, and hepatic steatosis were significantly increased after feeding rats with HCD.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus isolates reported to alleviate MAFLD include L. reuteri [ 120 ], L. plantarum [ 116 - 118 ], L. pentosus [ 119 ], L. rhamnosus [ 121 ], L. paracasei [ 114 , 115 ], L. gasseri [ 113 ], and Latilactobacillus sakei [ 122 ]. Generally, these isolates demonstrate the capability to reduce hepatic fat accumulation, suppress immune activation and improve intestinal barrier integrity.…”
Section: Icrobial Metabolites On Metabolic-associated Fatty Liver Dis...mentioning
confidence: 99%